Living Your Best Life: Lifestyle Medicine for All Women. Issue 5 (September 2022) - McHugh, John; Alexander, Megan; Kudesia, Rashmi; Krant, Jessica; Comander, Amy; Tollefson, Michelle; Geyer, Cynthia
In an era of ever-increasing healthcare expenditures, yet simultaneously worsening outcomes, many of our patients choose between traditional medical care or often unproven alternative therapies. While the recognition of lifestyle change in addressing cardiovascular and metabolic disease grows, there is less understanding of the impact of lifestyle change on issues facing women every day. Millions of women around the globe struggle with infertility, cancer, sexual dysfunction, and dermatologic needs. Yet, research on the benefits of lifestyle change on these conditions is scarce, and gaps exist both in our understanding of evidence-based approaches to address these issues, as well as adequate provider education when evidence exists. The Women's Health Member Interest Group convened medical experts in these areas that affect women's lives to provide insights and meaningful education applicable not only for our patients, but also in our own lives.